Comparative Financial Performance and Financial Soundness of Banks in Bhutan: Application of DuPont and Bankometer Models - Suresh, N.; Alphonnse Ligori,, T. Antony; Khan, Sadaf; Ahmad Khan, Shad (International Journal of Psychosocial Rehabilitation, 2024)
In the land of Gross National Happiness and a developing country like Bhutan, the banking system plays a robust role in ensuring sustainable and equitable economic development. Banks play a significant role and have a direct brunt on the economy in terms of return in the era of globalization. The performance of the financial sector over the period had improved with the continued expansion of its business. The credit growth accelerated over the years, and the bank's performance notably enhanced in terms of managing assets and increasing its returns. The banking sector expanded their branch network around the country, thereby increasing access to various financial services. The study aims to look at the financial performance of Bank of Bhutan Limited (BOB) and Tashi Bank (T-Bank) using DuPont analysis and the financial soundness of the banks being assessed through the Bankometer model for a period of six years (2012-2017). The bankometer model is the outcome of IMF (2000) guidelines for evaluating the financial soundness of banks. The findings of the study reveal that both banks had ensured financial performance and financial soundness. The present study would help shareholders, investors, and managers make better financial decisions.